SEMI-AUTOMATIC HONEY MACHINE WITH LOW PRESSURE SCREW GEARBOX HYDRAULIC SYSTEM - Adhitya Wira Dharma; Achmad Rianto; Andriyanti Achsan; Asrul Ludin; Ridwan Maulana (AIBPM Publisher, 2018)
The purpose of this study is to provide solutions to existing problems in SMEs Honey in the sector of Malang which is still using the traditional way in its process of filtering honey that has been applied. The method used is to utilize the Jack Screw system as an alternative to press and filter honey. In addition, it is also equipped with an ECU as a control system to regulate the working mechanisms exist. The expected result is to improve the quality of honey filtering so as to increase the productivity of SME Honey up to 400%. Early production of 3kg to 25kg of honey filtered every day